CuInS2 / Bi2O3 composite photocatalyst as well as preparation method and application thereof

By preparing the CuInS2/Bi2O3 composite photocatalyst and utilizing the heterojunction structure to promote the separation of photogenerated charges, the problem of poor photocatalytic effect in the existing technology was solved, and the efficient degradation of ciprofloxacin and wastewater treatment were achieved.

CN120644215APending Publication Date: 2025-09-16KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510811571.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-17
Publication Date
2025-09-16

AI Technical Summary

Technical Problem

Existing semiconductor materials have limited light absorption capacity and poor photogenerated carrier separation efficiency during the photocatalytic oxidation process, resulting in poor photocatalytic effect and difficulty in effectively removing ciprofloxacin from water.

Method used

The CuInS2/Bi2O3 composite photocatalyst was prepared by growing Bi2O3 nanosheets on CuInS2 nanospheres to form a heterojunction, which promoted the separation of photogenerated charges and improved the photocatalytic performance.

Benefits of technology

Efficient photocatalytic degradation of ciprofloxacin was achieved, with a degradation rate of up to 80%, which improved the wastewater treatment efficiency. The process is simple and has low energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120644215A_ABST
    Figure CN120644215A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of environmental material preparation, and particularly relates to a CuInS2 / Bi2O3 composite photocatalyst as well as a preparation method and application thereof. The CuInS2 / Bi2O3 composite photocatalyst disclosed by the invention comprises a CuInS2 nanosphere and a Bi2O3 nanosheet which is grown on the CuInS2 nanosphere, and a heterojunction is formed between the CuInS2 and the Bi2O3. Compared with a CuInS2 material, the CuInS2 / Bi2O3 composite photocatalyst has a better photocatalytic effect, can efficiently degrade ciprofloxacin-containing wastewater, is simple and convenient to operate, and is green and environment-friendly. Embodiments and application example data show that when the CuInS2 / Bi2O3-30 composite photocatalyst is used for photocatalytic degradation of ciprofloxacin, the ciprofloxacin degradation rate can reach 80% under the illumination condition, and excellent wastewater treatment efficiency is shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of environmental material preparation, and specifically relates to a CuInS2 / Bi2O3 composite photocatalyst and a preparation method and application thereof. Background Art

[0002] Ciprofloxacin is a typical antimicrobial drug, but it is not fully absorbed by organisms, resulting in approximately 40% to 60% excretion through metabolic pathways. Ciprofloxacin is highly resistant to light, heat, and oxidants, is difficult to degrade, is highly stable, and is biotoxic, making it difficult to completely remove by traditional water treatment processes. Consequently, residues ranging from ng / L to mg / L are frequently detected in water bodies. The continuous accumulation of ciprofloxacin in water bodies exacerbates the emergence and spread of antibiotic resistance genes, posing a serious threat to ecosystem safety and human health.

[0003] Research on how to efficiently remove the harmful substance ciprofloxacin from water bodies is of great significance to environmental protection. Traditional methods for treating pollutants in wastewater can be divided into physical, biological and chemical methods, but these traditional methods have disadvantages such as incomplete removal effect, long sewage treatment time and large reagent requirements. Advanced oxidation technology is used as a typical and efficient removal method for deep treatment of organic pollutants in water bodies, among which photocatalytic oxidation technology is an efficient and green oxidation process. In the photocatalytic oxidation process, semiconductor materials can generate holes with strong oxidizing properties and electrons with strong reducing properties, which can be directly used for the degradation of organic pollutants. However, due to the limited light absorption capacity of semiconductor materials, the separation efficiency of photogenerated carriers is poor, and the interfacial catalytic reaction is slow, there is a problem of poor photocatalytic effect in practical applications. Summary of the Invention

[0004] In view of this, the object of the present invention is to provide a CuInS2 / Bi2O3 composite photocatalyst and its preparation method and application. The CuInS2 / Bi2O3 composite photocatalyst of the present invention has good photocatalytic effect.

[0005] The present invention provides a CuInS2 / Bi2O3 composite photocatalyst, comprising CuInS2 nanospheres and Bi2O3 nanosheets grown on the CuInS2 nanospheres, wherein a heterojunction is formed between the CuInS2 nanospheres and the Bi2O3 nanosheets.

[0006] Preferably, the mass proportion of Bi2O3 in the CuInS2 / Bi2O3 composite photocatalyst is 20% to 40%.

[0007] The present invention also provides a method for preparing the CuInS2 / Bi2O3 composite photocatalyst described in the above technical solution, comprising the following steps:

[0008] A copper source, an indium source, a reducing organic solvent, a sulfur source and Bi2O3 are mixed to undergo a solvothermal reaction to obtain a CuInS2 / Bi2O3 composite photocatalyst.

[0009] Preferably, the mass ratio of the copper source to Bi2O3 is 0.3:0.074-0.197.

[0010] Preferably, the preparation method of Bi2O3 comprises the following steps: adding alkaline solution dropwise to a bismuth salt solution until the pH value reaches 10 to 12 to perform a precipitation reaction, and calcining the obtained precipitate to obtain Bi2O3.

[0011] Preferably, the calcination temperature is 400-600° C., and the holding time is 3-4 hours.

[0012] Preferably, the copper source includes copper nitrate, the indium source includes indium nitrate, and the sulfur source includes thiourea.

[0013] Preferably, the mass ratio of the copper source, indium source and sulfur source is 0.3:0.3-0.4:0.3-0.5.

[0014] Preferably, the temperature of the solvent thermal reaction is 150-250° C., and the time is 8-16 hours.

[0015] The present invention also provides the use of the CuInS2 / Bi2O3 composite photocatalyst described in the above technical solution or the CuInS2 / Bi2O3 composite photocatalyst obtained by the above preparation method in the photocatalytic degradation of organic pollutants.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] The present invention provides a CuInS2 / Bi2O3 composite photocatalyst, comprising CuInS2 nanospheres and Bi2O3 nanosheets grown on the CuInS2 nanospheres, wherein a heterojunction is formed between the CuInS2 nanospheres and the Bi2O3 nanosheets. CuInS2 is a direct bandgap semiconductor with a bandgap of approximately 1.5 eV, a wide spectral response range, and an easily adjustable bandgap width. The present invention utilizes a bismuth-containing photocatalyst Bi2O3 to modify CuInS2 to improve its photocatalytic performance, as Bi2O3 can induce photoelectron-hole pairing. The present invention composites CuInS2 with Bi2O3, promotes charge separation of the photocatalyst, and improves the quantum efficiency of CuInS2. The composite photocatalyst has unique morphological characteristics (heterojunction) and can utilize adsorption and photocatalytic generation of active oxygen mechanisms to effectively and quickly remove ciprofloxacin from water. The CuInS2 / Bi2O3 composite photocatalyst of the present invention has a good photocatalytic effect.

[0018] The data of the embodiments and application examples show that the CuInS2 / Bi2O3-30 composite photocatalyst is used to photocatalytically degrade ciprofloxacin, and the degradation rate of ciprofloxacin can reach 80% under light conditions, showing excellent wastewater treatment efficiency.

[0019] The present invention also provides a method for preparing the CuInS2 / Bi2O3 composite photocatalyst described in the above technical solution, which has a simple process and low energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0021] Figure 1 XRD patterns of the substrate materials CuInS2, Bi2O3, and composite photocatalyst CuInS2 / Bi2O3-30;

[0022] Figure 2 This is a SEM image of the substrate material CuInS2 prepared in Comparative Example 1;

[0023] Figure 3 This is a SEM image of the composite photocatalyst CuInS2 / Bi2O-30 prepared in Example 1;

[0024] Figure 4 This is a diagram showing the adsorption and degradation effects of ciprofloxacin on CuInS2, Bi2O3, CuInS2 / Bi2O3-20, CuInS2 / Bi2O3-30, and CuInS2 / Bi2O3-40 materials in Application Example 1;

[0025] Figure 5 This is a SEM image of the CuInS2 substrate material prepared in Comparative Example 2;

[0026] Figure 6 This is the SEM image of the composite photocatalyst CuInS2 / Bi2O3 prepared in Comparative Example 3. DETAILED DESCRIPTION

[0027] The present invention provides a CuInS2 / Bi2O3 composite photocatalyst, comprising CuInS2 nanospheres and Bi2O3 nanosheets grown on the CuInS2 nanospheres, wherein a heterojunction is formed between the CuInS2 nanospheres and the Bi2O3 nanosheets.

[0028] In the present invention, the mass proportion of Bi2O3 in the CuInS2 / Bi2O3 composite photocatalyst is preferably 20% to 40%, specifically 20%, 30%, or 40%. The mass proportion of Bi2O3 described in the present invention provides excellent photocatalytic performance. Too little bismuth oxide results in an insufficient number of active sites available for reaction, resulting in low separation efficiency of photogenerated electron-hole pairs and limited catalytic activity. Too much bismuth oxide may cause agglomeration, clogging the pores of the support, reducing the exposed active surface area, and reducing the number of effective active sites, resulting in decreased light utilization efficiency.

[0029] In the present invention, the Bi2O3 nanosheets preferably further include a small amount of inevitable simple Bi (formed by reduction of Bi2O3).

[0030] CuInS2 nanospheres contain no toxic or harmful elements and are chemically stable. Bi2O3 nanosheets have a large surface area, are non-toxic, low-cost, and easy to synthesize. The Bi2O3 band gap is approximately 2.7 eV, and they exhibit excellent photocatalytic activity under visible light. The CuInS2 / Bi2O3 composite photocatalyst of the present invention is a nanocomposite photocatalyst that effectively improves solar energy utilization and exhibits strong photocatalytic degradation of organic pollutants.

[0031] The present invention also provides a method for preparing the CuInS2 / Bi2O3 composite photocatalyst described in the above technical solution, comprising the following steps:

[0032] A copper source, an indium source, a reducing organic solvent, a sulfur source and Bi2O3 are mixed to undergo a solvothermal reaction to obtain a CuInS2 / Bi2O3 composite photocatalyst.

[0033] In the present invention, unless otherwise specified, the materials and equipment used are commercially available products in the art.

[0034] In the present invention, the copper source preferably includes copper nitrate, specifically Cu(NO3)·3H2O.

[0035] In the present invention, the indium source preferably includes indium nitrate, specifically In(NO 3 ) 3 ·H 2 O.

[0036] In the present invention, the reducing organic solvent preferably includes ethylene glycol.

[0037] In the present invention, the sulfur source preferably includes thiourea, and the mass ratio of the copper source, indium source and sulfur source is preferably 0.3:0.3~0.4:0.3~0.5, specifically 0.3:0.38:0.38; the amount ratio of the copper source, indium source, sulfur source and reducing organic solvent is preferably 0.3g:0.38g:0.38g:70mL.

[0038] In the present invention, the preparation method of Bi2O3 preferably includes the following steps: adding alkaline solution to a bismuth salt solution until the pH value is 10-12 to perform a precipitation reaction, and calcining the obtained precipitate to obtain Bi2O3.

[0039] In the present invention, the bismuth salt in the bismuth salt solution is preferably bismuth nitrate, specifically Bi(NO₃)·5H₂O. The solvent of the bismuth salt solution is preferably nitric acid (HNO₃), the concentration of the nitric acid is preferably 1.3 mol / L, and the ratio of Bi(NO₃)·5H₂O to nitric acid is preferably 6.5 g:100 mL.

[0040] In the present invention, the alkali solution is preferably a NaOH solution, and the concentration of the NaOH solution is preferably 1 mol / L.

[0041] In the present invention, the pH value of the system after the alkaline solution is added is preferably 11. The precipitation reaction is preferably carried out under ultrasonic conditions, and the ultrasonic time is preferably 1 hour.

[0042] In the present invention, after the precipitation reaction, the process preferably further comprises: solid-liquid separation, and the obtained solid is washed and dried in sequence; the solid-liquid separation method is preferably centrifugation, and the washing preferably comprises alternating water washing and ethanol washing, and the total number of alternating washings is preferably 6 times; the drying temperature is preferably 60°C, and the drying time is preferably 12 hours.

[0043] In the present invention, the calcination temperature is preferably 400-600° C., specifically 500° C., and the holding time is preferably 3-4 hours.

[0044] In the present invention, the mass ratio of the copper source to Bi2O3 is preferably 0.3:0.074 to 0.197, specifically 0.3:0.074, 0.3:0.125 or 0.3:0.197.

[0045] In the present invention, the molar ratio of Cu in the copper source to Bi in Bi2O3 is 1.2:0.12-0.46, specifically 1.2:0.27.

[0046] In the present invention, the copper source, indium source, reducing organic solvent, sulfur source and Bi2O3 are preferably mixed as follows: the copper source, indium source and reducing organic solvent are first mixed, then Bi2O3 is added for a second mixing, and then the sulfur source is added for a third mixing; the first mixing, the second mixing and the third mixing are preferably carried out under stirring conditions, the time for the first mixing is preferably 1h, and the speed of the first mixing stirring is preferably 400-500rpm; the second mixing is sufficient to uniformly disperse the Bi2O3, and the time for the third mixing is preferably 40min.

[0047] In the present invention, the solvothermal reaction temperature is preferably 150-250°C, specifically 200°C, the pressure is preferably 1.4-1.6 MPa, and the reaction time is preferably 8-16 hours, specifically 12 hours. The solvothermal reaction is preferably carried out in a polytetrafluoroethylene-lined reactor. During the solvothermal reaction, CuInS2 nanospheres are generated, Bi2O3 nanosheets are bonded to the CuInS2 nanospheres, and a small amount of bismuth oxide is inevitably reduced by ethylene glycol under high temperature and pressure to form elemental bismuth.

[0048] In the present invention, after the solvent thermal reaction, the process preferably further comprises: solid-liquid separation, washing, drying and grinding the obtained solid; the solid-liquid separation is preferably carried out by centrifugation.

[0049] The present invention also provides the use of the CuInS2 / Bi2O3 composite photocatalyst described in the above technical solution or the CuInS2 / Bi2O3 composite photocatalyst obtained by the above preparation method in the photocatalytic degradation of organic pollutants.

[0050] In the present invention, the organic pollutant preferably includes ciprofloxacin. The CuInS2 / Bi2O3 composite photocatalyst of the present invention can efficiently adsorb and degrade ciprofloxacin.

[0051] In order to further illustrate the present invention, the CuInS2 / Bi2O3 composite photocatalyst provided by the present invention, its preparation method and application are described in detail below with reference to the accompanying drawings and examples, but they should not be understood as limiting the scope of protection of the present invention.

[0052] Example 1

[0053] Weigh 6.5 g of Bi(NO3)·5H2O and dissolve it in 100 mL of 1.3 mol / L HNO3 solution, stir at 80°C for 30 min, then titrate with 1 mol / L NaOH solution until the pH value is 11, ultrasonicate for 1 h, then centrifuge, wash alternately with water and ethanol six times, dry in a vacuum drying oven at 60°C for 12 h, and finally calcine at 500°C (heating rate of 5°C / min) in a muffle furnace for 4 h to obtain the product Bi2O3.

[0054] After 0.3g Cu(NO3)·3H2O and 60mL ethylene glycol were mixed and dissolved, 0.38g In(NO3)3·H2O was added and stirred vigorously at 400rpm for 1h, 0.125g Bi2O3 prepared above was added and stirred and dispersed thoroughly, then 0.38g thiourea was weighed and stirred for 40min; the mixed solution was transferred to a 100mL polytetrafluoroethylene-lined reactor and heated at a temperature of 200℃ and a pressure of 1.4MPa for 12h. After the reactor was naturally cooled to room temperature, it was centrifuged, washed, dried at 60℃ for 12h, and ground to obtain a CuInS2 / Bi2O3 composite photocatalyst (denoted as CuInS2 / Bi2O3-30).

[0055] Comparative Example 1

[0056] After 0.3g Cu(NO3)·3H2O and 60mL ethylene glycol were mixed and dissolved, 0.38g In(NO3)3·H2O was added and stirred vigorously at 400rpm for 1h, then 0.38g thiourea was weighed and stirred for 40min; the mixed solution was transferred to a 100mL polytetrafluoroethylene-lined reactor and heated at 200℃ and 1.4MPa for 12h. After the reactor was naturally cooled to room temperature, it was centrifuged, washed, dried at 60℃ for 12h, and ground to obtain the base material CuInS2.

[0057] Photocatalyst structure and performance characterization results:

[0058] Figure 1 The base materials are CuInS2, Bi2O3 and the composite photocatalyst CuInS2 / Bi2O3-30( Figure 1 The XRD pattern of the CuInS2 / Bi / Bi2O3 composite photocatalyst (labeled as CuInS2 / Bi / Bi2O3 in Figure 2) is shown. Comparing the CuInS2 / Bi2O3-30 composite photocatalyst with the CuInS2 standard card, the Bi2O3 standard card, and the Bi standard card reveals that the characteristic peaks of the composite photocatalyst are essentially consistent with those of the other two standard cards, demonstrating the successful preparation of the composite photocatalyst.

[0059] Figure 2 This is the SEM image of the CuInS2 substrate material of Comparative Example 1. Figure 3 This is the SEM image of the composite photocatalyst CuInS2 / Bi2O3-30 of Example 1. Figure 2 It can be seen that the CuInS2 material is a spherical morphology formed by stacking nanosheets. Due to the combination of flake Bi2O3, the CuInS2 / Bi2O3 composite photocatalyst presents a flower-spherical morphology combined with nanosheets ( Figure 3 ), these nanosheets can provide additional active sites, thereby improving the performance of photocatalytic degradation reactions.

[0060] Example 2

[0061] The only difference from Example 1 is the amount of Bi2O3 added. In this example, 0.074 g is added, and the rest of the steps are the same.

[0062] The obtained composite photocatalyst was recorded as CuInS2 / Bi2O3-20.

[0063] Example 3

[0064] The only difference from Example 1 is the amount of Bi2O3 added. In this example, 0.197 g is added, and the rest of the steps are the same.

[0065] The obtained composite photocatalyst was recorded as CuInS2 / Bi2O3-40.

[0066] Application Example 1: Degradation of Ciprofloxacin

[0067] Light-protected stirring adsorption: 50 mg of CuInS2, Bi2O3, CuInS2 / Bi2O3-20, CuInS2 / Bi2O3-30, and CuInS2 / Bi2O3-40 catalyst materials were added to 100 mL of 20 mg / L ciprofloxacin solution, respectively. The samples were adsorbed in the dark for 30 min under magnetic stirring to reach an adsorption-desorption (saturation) state. The liquid samples were then collected using a syringe and immediately filtered through a 0.22 μm filter. The absorbance at a wavelength of 321 nm was measured using a UV-visible spectrophotometer.

[0068] Photocatalytic degradation: The solution after adsorption for 30 minutes was irradiated under a 500W xenon lamp. Samples were taken at intervals of 30 minutes, 60 minutes, 120 minutes, and 180 minutes, and filtered through a filter. The absorbance at a wavelength of 321 nm was measured using a UV-visible spectrophotometer.

[0069] According to the absorbance results, the adsorption and degradation efficiency of ciprofloxacin by different materials were calculated. The results are as follows: Figure 4 As shown. Figure 4 It can be seen that the adsorption and photocatalytic degradation efficiency of the composite photocatalyst of Example 1 is 80% (180 min), which is increased by 28% and 74% respectively compared with the adsorption and degradation efficiency of the base material CuInS2 of 52% and Bi2O3 of 6%.

[0070] When the Bi2O3 mass ratio is 40%, the loading is too high, resulting in poor adsorption performance and reduced light absorption effect, which inhibits the performance of the substrate material. When the Bi2O3 mass ratio is 30%, the composite photocatalyst has the best photodegradation effect on ciprofloxacin in water.

[0071] Comparative Example 2

[0072] 0.3 mmol CuCl and 0.3 mmol InCl3·4H2O were dissolved in 60 mL ethylene glycol, 3 mmol thioacetamide was added with stirring, and the mixture was stirred for 40 minutes. The mixture was transferred to a 100 mL polytetrafluoroethylene-lined reactor and heated at 200°C and 1.4 MPa for 12 hours. After the reactor was naturally cooled to room temperature, it was centrifuged, washed, dried at 60°C for 12 hours, and ground to obtain the base material CuInS2.

[0073] Comparative Example 3

[0074] 0.3 mmol CuCl and 0.3 mmol InCl3·4H2O were dissolved in 60 mL ethylene glycol, 0.06 mmol Bi2O3 was weighed and added to the solution, stirred and dispersed for 30 minutes, and then 3 mmol thioacetamide was added and stirred for 40 minutes. The mixture was transferred to a 100 mL polytetrafluoroethylene-lined reactor and heated at 200°C and 1.4 MPa for 12 hours. After the reactor was naturally cooled to room temperature, it was centrifuged, washed, dried, and ground to obtain the CuInS2 / Bi2O3 composite material.

[0075] Photocatalyst structure characterization:

[0076] Figure 5 This is the SEM image of the CuInS2 substrate material of Comparative Example 2. Figure 6 The SEM image of the composite photocatalyst CuInS2 / Bi2O3 of comparative example 3 is shown in FIG. Figure 5 It can be seen that the CuInS2 material is agglomerated nanoflower clusters. Due to the combination of flake Bi2O3, the CuInS2 / Bi2O3 composite photocatalyst presents an irregular morphology ( Figure 6 ), the photocatalytic performance of the material is reduced due to agglomeration and stacking of irregular morphologies.

[0077] Although the above embodiments provide a detailed description of the present invention, they are only part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on the embodiments of the present invention without creative work, and these embodiments all fall within the scope of protection of the present invention.

Claims

1. A CuInS2 / Bi2O3 composite photocatalyst, characterized in that: The invention comprises CuInS2 nanospheres and Bi2O3 nanosheets grown on the CuInS2 nanospheres, wherein a heterojunction is formed between the CuInS2 nanospheres and the Bi2O3 nanosheets.

2. The CuInS2 / Bi2O3 composite photocatalyst according to claim 1, characterized in that The mass proportion of Bi2O3 in the CuInS2 / Bi2O3 composite photocatalyst is 20% to 40%.

3. The method for preparing the CuInS2 / Bi2O3 composite photocatalyst according to claim 1 or 2, characterized in that: The following steps are involved: A copper source, an indium source, a reducing organic solvent, a sulfur source and Bi2O3 are mixed to undergo a solvothermal reaction to obtain a CuInS2 / Bi2O3 composite photocatalyst.

4. The preparation method according to claim 3, characterized in that The mass ratio of the copper source to Bi2O3 is 0.3:0.074-0.

197.

5. The preparation method according to claim 3 or 4, characterized in that The preparation method of Bi2O3 comprises the following steps: adding alkaline solution dropwise to a bismuth salt solution until the pH value reaches 10-12 to perform a precipitation reaction, and calcining the obtained precipitate to obtain Bi2O3.

6. The preparation method according to claim 5, characterized in that The calcination temperature is 400-600° C., and the heat preservation time is 3-4 hours.

7. The preparation method according to claim 3, characterized in that The copper source includes copper nitrate, the indium source includes indium nitrate, and the sulfur source includes thiourea.

8. The preparation method according to claim 3 or 7, characterized in that The mass ratio of the copper source, the indium source and the sulfur source is 0.3:0.3-0.4:0.3-0.

5.

9. The preparation method according to claim 3, characterized in that The temperature of the solvent thermal reaction is 150-250° C., and the time is 8-16 hours.

10. Use of the CuInS2 / Bi2O3 composite photocatalyst according to claim 1 or 2 or the CuInS2 / Bi2O3 composite photocatalyst obtained by the preparation method according to any one of claims 3 to 9 in photocatalytic degradation of organic pollutants.